If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = 6 + -4m Solving -10 = 6 + -4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '4m' to each side of the equation. -10 + 4m = 6 + -4m + 4m Combine like terms: -4m + 4m = 0 -10 + 4m = 6 + 0 -10 + 4m = 6 Add '10' to each side of the equation. -10 + 10 + 4m = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 4m = 6 + 10 4m = 6 + 10 Combine like terms: 6 + 10 = 16 4m = 16 Divide each side by '4'. m = 4 Simplifying m = 4
| 10*7=n*10 | | 5p-1=2p+20 | | 5n-14n=81 | | -3x+4=9 | | 4z+8=40 | | 8p+2=4p-10 | | 7*(8+2)=n | | 21.21+p=-101.6 | | 5r-7=38 | | 3x-21=5 | | 3(3-x)-5(-4-11x)= | | b^3-6b^2-6b=0 | | k+11=-21 | | 4(3-4x)=-148 | | -8z=32 | | 6-t=5 | | x+6+2x=15 | | 12=3n+3 | | W+3=11 | | 36=2(3w)+2w | | 6(7x+3)= | | 316-36=x | | 3*(4*2)=(n*16) | | -5n-9=4n+2 | | -4(x-7)+6(7x-7)=-52 | | pula^2-pula=0 | | 17-3p=16-4p | | 2(x+7)=8x-4 | | X+14-5=6 | | 4x-6=x+30 | | 2x+4(x+5)=9x-10 | | n+3(n-2)=10.4 |